UVA Photoactivation of Harmol Enhances Its Antifungal Activity against the Phytopathogens Penicillium digitatum and Botrytis cinerea - Olmedo, Gabriela M.; Cerioni, Luciana; González, María M.; Cabrerizo, Franco M.; Volentini, Sabrina I.; Rapisarda, Viviana A. (Frontiers in Microbiology, 2017)
Phytopathogenic fungi responsible for postharvest diseases on fruit and vegetables cause important economic losses. We have previously reported that harmol (1-methyl-9H-pyrido[3,4-b]indol-7-ol) is active against the causal agents of green and gray molds Penicillium digitatum and Botrytis cinerea, respectively. Here, antifungal activity of harmol was characterized in terms of pH dependency and conidial targets; also photodynamic effects of UVA irradiation on the antimicrobial action were evaluated. Harmol was able to inhibit the growth of both postharvest fungal disease agents only in acidic conditions (pH 5), when it was found in its protonated form. Conidia treated with harmol exhibited membrane integrity loss, cell wall disruption, and cytoplasm disorganization. All these deleterious effects were more evident for B. cinerea in comparison to P. digitatum. When conidial suspensions were irradiated with UVA in the presence of harmol, antimicrobial activity against both pathogens was enhanced, compared to non-irradiated conditions. B. cinerea exhibited a high intracellular production of reactive oxygen species (ROS) in the presence of harmol in irradiated and non-irradiated treatments. P. digitatum showed a significant increase in ROS accumulation only when treated with photoexcited harmol. The present work contributes to unravel the antifungal activity of harmol and its photoexcited counterpart against phytopathogenic conidia, focusing on ROS accumulation which could account for damage on different cellular targets.